Manajemen Peningkatan Mutu Pendidikan di Universitas Islam Jember - Mubarok, Rifki; Muhith, Abd.; Muis, Abdul (Jayapangus Press, 2024)
The low quality of education in Indonesia has actually been a long discussion. But until now the problem of education quality has not been resolved. Quality education is the hope and demand of all education stakeholders. This research is a type of qualitative research, so that with this approach can be obtained in-depth understanding and interpretation of the quality assurance system at the Islamic University of Jember. Based on the results of the study, it can be concluded that: (1) the management of educational quality improvement at the Islamic University of Jember is created and maintained in the quality management system of the Islamic University of Jember. The quality management system is a process of setting standards and managing compliance consistently and continuously so as to obtain stakeholder satisfaction. The system is contained in the quality manual integrated in the system documents at the Islamic University of Jember, which include: a) quality statement, b) quality policy, c) implementing unit, d) quality standards, e) quality procedures, f) work instructions, and g) quality objectives. Staging of quality objectives. (2) Furthermore, the implementation of the quality management system of the Islamic University of Jember uses the PDCA (plan, do, check, and action) quality control management model as stated in the policy documents and quality standards of the Islamic University of Jember.